The Reasons Why Organisations Outsource Information Technology Systems - Davis, Peter; Knox, I. (Australian Institute of Project Management, 2004)
The practice of outsourcing business is international with outsourcing of information technology (IT) systems leading the outsourcing phenomena. In Australia outsourcing is consistent with international trends. Detailed research concludes that organisations contemplate IT outsourcing for essentially thirteen reasons that fall within five categories. These categories represent financial, business, technical, political and environmental reasons. The research conducted concludes with key observations that include; outsourcing of IT systems is widespread, senior management are typically involved in outsourcing decision making processes. These managers have a good understanding of the concepts supporting outsourcing and are able to provide sound management practice towards planning for the introduction of outsourcing. It is found that functions that are repetitive, operational in nature or of less strategic importance, tend to be outsourced. Determination of the top six reasons to outsource validated this assessment. Finally it is noted that five of the top six reasons nominated by the respondents fall within the context of business and technical reasons.